PERKOTAAN PASURUAN DI ERA KOLONIAL BELANDA PADA SEKITAR ABAD XVIII S.D. XIX - Muhammad Chawari (BRIN, 2002)
At the beginning of its existence, Pasuruan was a traditional city that developed due to the influence of the cultural centers that developed around it. These cultural centers include the Singasari Kingdom, the Blambangan Kingdom, the Majapahit Kingdom, and the Mataram Kingdom. In addition, there is a traditional port, which was developed due to the presence of traders from around Pasuruan. The traditional city is centered on a plaza with the regent's office located to the north of the square. Apart from the existence of the Grand Mosque which is located west of the square. Apart from local traders, there are also foreign traders. One of these foreign traders was the Netherlands. The Dutch traders then settled and subsequently made their own colonies according to their interests, namely to maintain their existence. With the presence of foreign traders who settled down, their settlements emerged - eventually becoming a city with all its facilities and amenities.